1995
DOI: 10.1103/physrevb.52.10452
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Pr and Gd ordering in the 2212-type compounds (Pb0.5Cu0.5

Abstract: Magnetic and calorimetric measurements have been made to reveal a Pr ordering in the (Pb05Cuo, )2{Bao, Sro, )&PrCu20g compound which has the {Pb,Cu)-2212-type tetragonal structure with 0 0 lattice parameters a = 3.878(3) A and c =27.594(9) A. The transition occurs at a relatively high Tz{Pr } of 9 K. In comparison, isostructural (Pbo 5Cuo &)2 (Bao 5Sro 5)2GdCu&O, exhibits a T&{od) of only 2.2 K.The magnetic entropy associated with the Pr ordering has a lower limit value equivalent to about 20% of Rln3 expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…So far, the Tl-1212 type Tl(Ba,Sr) 2 PrCu 2 O 7 , (Pb,Cu)-1212 type (Pb,Cu)Sr 2 PrCu 2 O 7 , Hg-1212 type HgSr 2 PrCu 2 O 7 , Nb-1212 type NbBa 2 PrCu 2 O 7 , and Cu-123 type Pr(Ba,R) 2 Cu 3 O 7 (R ¼ La, Pr) nonsuperconducting compounds also exhibit the common feature of having anomalous T N (Pr) values ranging from 2 to 17 K [7][8][9][10][11][12][13][14][15][16][17][18]. Other 2212-type compounds with T N (Pr) of 9 K for (Pb,Cu)-2212 (Pb 0.5 Cu 0.5 ) 2 (Ba 0.5 Sr 0.5 ) 2 PrCu 2 O 8 and 17 K for Cu-2212 PrBa 2 Cu 4 O 8 , and another 3212-type compound, with T N (Pr) of 6-14 K for (Pb,Cu)-3212 (Pb 2 Cu)(Ba,Sr) 2 PrCu 2 O 8 were also observed [19][20][21][22] [25][26][27]. Hence, this seems to suggest that a correlation exists between the suppression of superconductivity and anomalous Pr magnetism in high-T c cuprates.…”
Section: Introductionmentioning
confidence: 89%
“…So far, the Tl-1212 type Tl(Ba,Sr) 2 PrCu 2 O 7 , (Pb,Cu)-1212 type (Pb,Cu)Sr 2 PrCu 2 O 7 , Hg-1212 type HgSr 2 PrCu 2 O 7 , Nb-1212 type NbBa 2 PrCu 2 O 7 , and Cu-123 type Pr(Ba,R) 2 Cu 3 O 7 (R ¼ La, Pr) nonsuperconducting compounds also exhibit the common feature of having anomalous T N (Pr) values ranging from 2 to 17 K [7][8][9][10][11][12][13][14][15][16][17][18]. Other 2212-type compounds with T N (Pr) of 9 K for (Pb,Cu)-2212 (Pb 0.5 Cu 0.5 ) 2 (Ba 0.5 Sr 0.5 ) 2 PrCu 2 O 8 and 17 K for Cu-2212 PrBa 2 Cu 4 O 8 , and another 3212-type compound, with T N (Pr) of 6-14 K for (Pb,Cu)-3212 (Pb 2 Cu)(Ba,Sr) 2 PrCu 2 O 8 were also observed [19][20][21][22] [25][26][27]. Hence, this seems to suggest that a correlation exists between the suppression of superconductivity and anomalous Pr magnetism in high-T c cuprates.…”
Section: Introductionmentioning
confidence: 89%
“…Identifying the role of each constituent in superconducting compounds provides an indirect route of recognizing the origin of superconductivity. Among them, cation substitution of Ca in Bi-2212 compound has been studied extensively [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. For example, it has been reported that the superconducting temperature of Bi-2212 was reduced by replacing Ca with other rare earth elements, such as Gd 3+ [4,5], Ce 3+ [6] and La 3+ [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that the superconducting temperature of Bi-2212 was reduced by replacing Ca with other rare earth elements, such as Gd 3+ [4,5], Ce 3+ [6] and La 3+ [7,8]. In particular, the Pr-substituted cuprate was found to show some anomalies on its antiferromagnetic transition temperature [9][10][11]. The real cause for such phenomenon has not been clearly identified because most of the polycrystalline Pr-doped Bi-2212 samples used in the studies are often found to be inhomogeneous [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%